Sosialisasi Tentang Pencegahan Gizi Buruk dalam Upaya Meningkatkan Kesehatan Ibu dan Anak - Anwar, Hairil; Hardilina; Rasidar; Apriyanto, Dhidik; Marini (JPM: Jurnal Pengabdian Masyarakat, 2024)
Central Village, Mempawah Hilir District, Mempawah Regency, still has malnutrition sufferers. There are 24 malnourished children in the region. This is the concern of the Mempawah Regency government in dealing with malnutrition sufferers, Kelurahan Tengah is an urban area close to the decision-making centre. Several problems trigger malnutrition in Central Village, including mothers who have children rarely go to Posyandu to weigh children, so children under five who experience weight loss are not immediately anticipated, then non-health factors in the form of poverty, social, cultural, education, and infrastructure, and health factors in the form of poor community nutrition knowledge. The purpose of this community service is to educate mothers who have children under five knowledge about the importance of nutritious food intake for toddlers to become healthy and smart children, as well as knowledge about supplementary feeding (PMT) as an effort to overcome malnutrition such as (MP-ASI) and PMT Recovery of Malnutrition with local specialities.  PKM partners are families (mothers who have children under five/mothers who have children under five who suffer from malnutrition). The method of implementing PKM is in the form of lectures, and discussions. PKM results show that most partners (90%) understand the material presented in socialisation activities. Most partners can answer questions about knowledge about nutrition and complementary feeding (MP-ASI) as well as supplementary feeding (PMT) post-malnutrition recovery to meet balanced nutrition for children under five.